Spatial Analysis of Regional Inequalities in Turkey - Ferhan Gezici; Geoffrey Hewings (European Regional Science Association (ERSA), 2003)
In this paper, we examine regional inequalities in Turkey not only at the inter-provincial level but for three different regional definitions as well. The motivation draws on the findings of Gezici and Hewings(2001) that raised questions about inequalities not only between regions (inter-regional) but inequalities within each region. Hence, one contribution of this paper is to test the effects of aggregation and scale on the identification of regional inequalities. Spatial data analysis is employed to examine the spatial dimension of inequality in Turkey and the relationship between spatial dependence and the dynamics of growth. The results indicate that overall inequalities are decreasing, however spatial dependence is becoming more dominant. The Theil index indicates that interregional inequalities are increasing while intra-regional inequalities are declining for all spatial partitions from 1980 to 1997. Most developed provinces are enhancing overall inequalities, although there is some evidence of a spread effect on their neighbors.
Keywords: 330